Sujok triorigin therapy for vaginitis: case reports - Nurjannah, Intansari (International Journal of Research in Medical Sciences, 2023)
Vaginitis cases are the most frequently encountered cases of gynaecologists in women who seek treatment at health facilities. Various therapies are sought by sufferers to overcome this condition. This case report discusses the use of Sujok triorigin therapy with the mudra method to treat the symptoms of vaginitis. Mudra method is the therapy only by using the thumb placed on certain knuckles based on the tri-origin concept and the respondents meditate for 15-20 minutes. There was no charge applied for the therapy were given to the patient. Two female patients on their 40s contacted researcher through social media to get help for their vaginitis problems. Researcher sent the instruction through picture how to apply the therapy on patients’ fingers. In the first case, this extreme vaginal itching condition had been experienced for 1 year with various treatment methods tried but none were successful. In this respondent, it took 9 days for the itching to completely disappear with therapy being done 4 times a day for about 15 minutes. The second respondent complained of extreme itching in the vagina, with a severity scale of 5 (from 1-5) and bleeding because of scratching. After 4 minutes of doing mudra, the itching went down to scale 3 and after 20 minutes the itching went down to a score of 1-2 and then was completely gone after that. In conclusion, Sujok triorigin therapy can reduce vaginitis symptoms in two respondents in a relatively short time of therapy.